PENERAPAN SMALL GROUP DISCUSSION UNTUK MENINGKATKAN KEAKTIFAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SISWA SMP MUHAMMADIYAH 7 SUMBERLAWANG - Saptono Saptono; Muhammad Ja’far Nashir (Jurnal Manajemen Pendidikan, 2026)
This study described the implementation of the Small Group Discussion method, identified forms of student activeness, and analyzed supporting and inhibiting factors in Islamic Religious Education learning at SMP Muhammadiyah 7 Sumberlawang, Sragen Regency, during the 2025/2026 academic year. It employed a qualitative approach with a field research design. Informants included an Islamic Religious Education teacher, students, the principal, and a Muhammadiyah figure. Data were collected through observation, semi-structured interviews, and documentation. Data credibility was established through source and technique triangulation, while analysis involved data condensation, data display, conclusion drawing, and verification. The findings showed that the method was implemented through communicating objectives and materials, forming heterogeneous groups of four students, assigning topics, conducting discussions, teacher facilitation, presentations, reinforcement, and conclusions. The method encouraged students to ask questions, express opinions, answer questions, collaborate, present results, and summarize material. Supporting factors included enthusiasm, textbooks, worksheets, Smart TV, and principal support. Barriers included low self-confidence, unequal academic ability, domination, and limited time.